2012
DOI: 10.1002/pi.4409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,4‐cyclohexylene units on thermal properties of poly(1,4‐cyclohexylenedimethylene adipate) and similar aliphatic polyesters

Abstract: In the field of aliphatic polyesters there is a great interest in building novel macromolecular structures that may effectively feature the required properties for specific applications. For this reason, it is extremely important to understand the correlations between chemical structure and final performance. Monomers based on the 1,4‐cyclohexylene unit are interesting as they are potentially bio‐based and rigid enough to improve glass transition and melting temperatures. The present paper describes the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…The homopolymer sample was prepared following the literature, by a two‐stage process, from dimethyl adipate and 1,4‐cyclohexanedimethanol with 66 mol % of trans isomer content.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The homopolymer sample was prepared following the literature, by a two‐stage process, from dimethyl adipate and 1,4‐cyclohexanedimethanol with 66 mol % of trans isomer content.…”
Section: Methodsmentioning
confidence: 99%
“…A new polymeric matrix was chosen for this study: the poly(1,4‐dimethylcyclohexane adipate), an aliphatic polyester prepared from dimethyl adipate and 1,4‐cyclohexanedimethanol (CHDM), potentially biobased and biodegradable . Indeed, although such monomers are now petro‐derived, the processes to prepare them from biomass are available .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Celli et al. synthesized a series of poly(1,4‐cyclohexylenedimethylene‐1,4‐cyclohexanedicarboxylate) (PCCD) and found that the T m of PCCD could be varied from 128 °C for the polyester containing 99% trans ‐CHDA (1,4‐cyclohexanedicarboxylic acid) to 104 °C for the polyester synthesized from 70% cis ‐CHDA . They also changed the amorphous poly(butylene 1,4‐cyclohexanedicarboxylate) (PBCHD) to highly crystalline polyester only by increasing the trans ‐CHDA content from 26% to 100% .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the glass transition ( T g ) and melting ( T m ) temperatures of polymers containing 1,4‐cyclohexylene moieties are higher with respect to those of the corresponding polyesters with linear aliphatic groups like poly(butylene adipate). Both CHDA and CHDM are obtained from terephthalic acid that can be prepared starting from renewable resources, making these monomers attracting from an environmental point of view .…”
Section: Introductionmentioning
confidence: 99%